Implementasi JST Dalam Menentukan Kelayakan Nasabah Pinjaman KUR Pada Bank Mandiri Mikro Serbelawan Dengan Metode Backpropogation - Windarto, Agus Perdana (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The purpose of this study was to develop a decision support system that can facilitate in determining the eligibility of borrowers KUR (Kredit Usaha Rakyat) through predictive use based on existing data and presents various alternative solutions in the selection of a feasibility customers in KUR loan. This study uses Artificial Neural Network applications using Backpropogation method. Criteria used as an assessment in this study is Collateral, Capacity, Loan Application Form, Income and Establishment Business License (Business License). The decision making process consists of two (2) phases where the first phase and pattern recognition, the second phase is forecast feasibility KUR customers. pattern recognition and predictive feasibility KUR customers using different data with the same process using training and testing. The conclusion by the two architectural models 5-2-1 and 5-3-1, obtained 93% accuracy with 0.0009995807 MSE is the 5-2-1 model architecture. This model is used to predict the feasibility of KUR customers with accuracy> 90% and MSE truth 0.0009566280.